Peningkatan Pengetahuan Pengendalian Vektor Penyebab Demam Berdarah Dengue Pada Wilayah Kasus Tinggi di Kota Palu, Sulawesi Tengah - Devi Oktafiani; Intania Riska Putrie; Ryka Marina Walanda; Tri Setyawati; Listawati Listawati (BERDAYA: Jurnal Pendidikan dan Pengabdian Kepada Masyarakat, 2025)
Controlling the population of mosquitoes that cause Dengue Fever is one of the efforts to reduce the incidence of dengue virus infection. The purpose of this service is to increase the knowledge and understanding of the community in areas with high cases in Palu City. It is hoped that by increasing knowledge, DHF cases in the region will decrease and reduce morbidity rates. The method used is socialization about vector control and understanding the clinical conditions of dengue fever to anticipate high mortality cases caused by dengue virus infection. By increasing knowledge about how to eradicate the vector that causes dengue fever, it is hoped that the community can eradicate the Aedes aegypti mosquito vector massively. The stages in increasing knowledge and implementing dengue vector control are the introduction of 3M plus, signs and symptoms of dengue fever, when to see a doctor or health center and initial treatment if dengue symptoms arise. It is hoped that these habits can be applied starting from the school and family environment. From the design above, it is hoped that the output of this activity is an increase in knowledge about how to control dengue vectors and can reduce morbidity and mortality in areas with high dengue cases.